Implementasi Program Mu'adalah Di Pondok Pesantren Baitul Arqom Balung Kabupaten Jember: Implementation of the Mu'adalah Program at Baitul Arqom Islamic Boarding School, Balung, Jember Regency - Imron Fauzi (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2018)
Although the Indonesian government has recognized the equality of Islamic boarding schools through Minister of Religious Affairs Regulation No. 18 of 2014, the standardization of Mu’adalah pesantren education still faces various implementation challenges. This study aims to analyze the implementation, problems, and impacts of the Mu’adalah program at Baitul Arqom Balung Islamic Boarding School in Jember Regency. Using a descriptive qualitative approach with snowball sampling, data were collected through interviews, observation, and documentation. The findings indicate that program implementation has followed national education standards except for assessment, financing, and management standards. Key problems include administrative issues, evaluation, financing, certification, and teacher qualifications. Positive impacts include increased public trust and access to government assistance, although technical constraints remain significant. This study recommends improving administrative technical guidelines and teacher welfare. Meskipun pemerintah telah mengakui kesetaraan pesantren melalui Peraturan Menteri Agama No. 18 Tahun 2014, standarisasi pendidikan pesantren Mu’adalah masih menghadapi berbagai kendala implementasi. Penelitian ini bertujuan menganalisis implementasi, problematika, dan dampak program Mu’adalah di Pondok Pesantren Baitul Arqom Balung Kabupaten Jember. Menggunakan pendekatan kualitatif deskriptif dengan teknik snowball sampling, data dikumpulkan melalui wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa implementasi program telah mengikuti standar nasional pendidikan kecuali pada standar evaluasi, pembiayaan, dan manajemen. Problematika utama meliputi administrasi, evaluasi, pembiayaan, sertifikasi, serta kualifikasi guru. Dampak positifnya adalah meningkatnya kepercayaan masyarakat dan terbukanya akses bantuan pemerintah, meskipun kendala teknis masih signifikan. Penelitian ini merekomendasikan penyempurnaan petunjuk teknis administratif dan peningkatan kesejahteraan guru.